Analisis Peningkatan Efektivitas Dalam Perencanaan Pengembangan Pembangunan: Studi Kasus : di Pulau Dompak Tanjunginang - Aisyah Aisyah; Nana Amelia Sefti (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Tanjungpinang is the capital city of Riau Islands province, Indonesia and is an autonomous city formed in 2004. The development of Tanjungpinang city, especially in the Dompak Island area which is designated as the center of government of Riau Islands Province, needs to be evaluated. This evaluation is useful for knowing and analyzing the problems that occur on Dompak Island, which will later be made improvement efforts so that the goals that have been set can be achieved properly. This research aims to identify and predict something that will happen and the continued performance carried out on Dompak Island, Riau Islands. The method used in this analysis is to use the literature study method as a data search technique by collecting several references from related books. Implementation of development plans must be done carefully and purposefully. Intensive monitoring and periodic evaluation must be carried out to ensure that development programs can run according to the original plan. In conclusion, the analysis of increasing effectiveness in development planning in the Dompak area of Tanjungpinang is very important. Through identification of the potential and needs of the region, collaboration between various related parties, and careful implementation, development in this area can run better and provide optimal benefits for the local community.